The impact of personality and leadership styles on leading change capability of Malaysian managers - Alkahtani, Ali Hussein; Abu-Jarad, Ismael; Sulaiman, Mohamed; Nikbin, Davoud (New South Wales Research Centre Australia (NSWRCA)., 2011)
This study was conducted to investigate the influence of the Big Five Dimensions of personality of the Malaysian Managers and the leadership styles these managers use on their leading change capabilities. Total sample of 105 managers was used in this study. The results of this study revealed that the Malaysian managers tend to enjoy personalities that are conscious and open to experience. These managers tend to use consultative leadership style. However, they use autocratic, democratic and some of them use laissez-fair, but the respondents of this study scored higher in consultative leadership style. The results of the study showed that Extroversion personality trait as well as involvement leadership style were positively related with Leading Change. Both Openness to Experience and Emotional Stability were significantly and positively correlated with Consultative Leadership Style that the managers use. Involvement Leadership Style was found to be significantly and positively correlated with Leading Change (R2=.38) In conclusion, this study showed a positively significant correlation between personality of managers, their leadership styles and their leading change capabilities